Penegakan Hukum Pelanggaran Lalu Lintas Merokok Saat Berkendara Oleh Satuan Lalu Lintas Polresta Bukittinggi - Aziz, Muhammad Abdul (Law, Development and Justice Review, 2024)
The development of road transport infrastructure has an important role in supporting economic activities, but on the other hand it gives rise to various problems regarding traffic law violations, accidents, etc. To prevent this, law enforcement officers are needed who have the authority and responsibility for state security and order, namely the State Police of the Republic of Indonesia as stated in their main duties, namely Law Number 2 of 2022 concerning the State Police of the Republic of Indonesia. Motor vehicle accident cases that occur in Indonesia have attracted a lot of public attention. One of them is caused by the driver not focusing when driving the vehicle. An action that is often carried out by motorbike riders is smoking while driving. There are already regulations prohibiting smoking while driving, which are contained in the Regulation of the Minister of Transportation of the Republic of Indonesia Number 12 of 2019 Article 6C. The research will analyze the law enforcement process for smoking while driving traffic violations by the Bukittinggi Police Traffic Unit and its obstacles and efforts to overcome these obstacles. This research includes library research, the approach method is empirical juridical, in the real sense and examines the law in society and how the law relates to society. The data required is primary and secondary data, collected through interviews, documents and literature review. The results of the research show that the public does not yet have the awareness of smoking-free driving, while the law enforcement provided by the police is only limited to warnings, this makes drivers continue to commit traffic violations due to the lack of strict law enforcement provided. Even though the regulations exist, law enforcement is still weak, in terms of community habits and law enforcement officers.